2008
DOI: 10.2320/matertrans.mra2008019
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of WC-SiC Whisker Composites by Hot Pressing and Their Mechanical Properties

Abstract: Composites of WC and SiC whisker (0-30 vol% SiC) were prepared at 1550 to 1800 C by using a resistance-heated hot pressing technique called spark plasma sintering. The composites obtained were examined for reaction products and microstructure, and were characterized for mechanical properties. The addition of small amounts of SiC induced the marked grain growth of WC, and drove the densification of WC. Above 10 vol% SiC, dispersed SiC phases impeded the grain growth of WC. Increasing sintering temperature made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Sintering of WC required a temperature of 1800 C to obtain a fully dense sintered body with a bulk density of 15.70 Mg m À3 , 4) which agrees with the previously determined X-ray density of 15.669 Mg m À3 . 18) However, WC-5 vol% SiC W (base ceramic) could be densely hot pressed at 1650 C. In the sintered base ceramic and Cr 3 C 2 -added ceramics, XRD analyses showed some evidence of a W 5 Si 3 phase that was not observed in the V 8 C 7 -or Cr 3 C 2 and V 8 C 7 -added ceramics.…”
Section: Bulk Densitysupporting
confidence: 74%
See 3 more Smart Citations
“…Sintering of WC required a temperature of 1800 C to obtain a fully dense sintered body with a bulk density of 15.70 Mg m À3 , 4) which agrees with the previously determined X-ray density of 15.669 Mg m À3 . 18) However, WC-5 vol% SiC W (base ceramic) could be densely hot pressed at 1650 C. In the sintered base ceramic and Cr 3 C 2 -added ceramics, XRD analyses showed some evidence of a W 5 Si 3 phase that was not observed in the V 8 C 7 -or Cr 3 C 2 and V 8 C 7 -added ceramics.…”
Section: Bulk Densitysupporting
confidence: 74%
“…The Young's modulus for both the 5 µm separate V 8 C 7 addition and the simultaneous Cr 3 C 2 and V 8 C 7 addition decreased with GGI content. The calculated Young's modulus, determined by the volumetric proportion of each component using 702 GPa for WC, 4) 440 GPa for hot-pressed SiC, 24) 370 GPa for Cr 3 C 2 25) and 430 GPa for V 8 C 7 , 25) remained nearly the same due to the relatively small amounts of GGI. The V 8 C 7 addition resulted in the largest decrease in Young's modulus.…”
Section: Mechanical Propertiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, most of W 2 C found in the sintered WC must have been caused by surface oxidation of the fine WC starting powder and the decarburization reaction during sintering, as described previously. 20) Zhao et al indicated that the W 2 C phase formed during sintering due to the existence of WO 3 layers on WC particles by the following reactions:…”
Section: Methodsmentioning
confidence: 99%